ANALISIS TEOLOGIS IMPLEMENTASI MANAJEMEN DALAM GEREJA - Watofa, Adolina Jaquelina Diana; Marini, Roberth Ruland; Santoso, D.S. Budiono (Sekolah Tinggi Teologi Sabda Agung, Surabaya, 2023)
This research discusses Christian Church management, which seeks to establish the biblical and theological foundations of church management and suggests several theological principles so that management can function as the best solution to the problem of ineffective resource management. In this way the church can manage every problem in the church properly and correctly based on the Bible.The purpose of this research is to outline what is needed to manage a church well and correctly based on the Bible. Thus, the results of this research explore each of the four main managerial functions, namely; planning, organizing, staffing and directing from a Biblical perspective. In conclusion, this research states that God is the creator of reasonable and effective managerial principles. Therefore, there is nothing wrong with using Biblically based managerial skills in managing what God has entrusted to the care of the church.